Digital image correlation strain measurement of ultra-high-performance concrete-prisms under static and cyclic bending-tensile stress - Harenberg, Stefan (2019)
This paper provides experimental results on investigations for the validation of photogrammetric strain measurements of ultra-high-performance concrete (UHPC)-prisms subjected to static and cyclic bending-tensile stress. For this purpose, 4 static and 5 cyclic test series were performed. Damage progresses during loading are monitored by means of a digital image correlation (DIC) system and a clip gauge. The control of the DIC by trigger lists and the measurement noise as a function of the measurement rate are examined. All static tests were performed force controlled with the same testing speed and the same measuring rate of DIC and clip gauge. All cyclic tests were performed with the same upper and lower stress levels but with different loading rates. During the static tests, the DIC can be used to make accurate strain measurements before UHPC failure. In the cyclic tests, the measurement noise of the DIC decreases with an increasing measuring rate. The tests performed confirm the control of the DIC by trigger lists for cyclic tests on UHPC-prisms and show that the measurement noise is negligible in static and cyclic tests.